Transactions on engineering technologies World Congress on Engineering and Computer Science 2014 - Kim, Haeng-Kon; Amouzegar, Mahyar A.; Ao, Sio-Iong (Springer Netherlands, 2015)
This volume contains thirty-nine revised and extended research articles, written by prominent researchers participating in the World Congress on Engineering and Computer Science 2014, held in San Francisco, October 22-24 2014. Topics covered include engineering mathematics, electrical engineering, circuit design, communications systems, computer science, chemical engineering, systems engineering, and applications of engineering science in industry. This book describes some significant advances in engineering technologies, and also serves as an excellent source of reference for researchers and graduate students.